(untitled) (Veterinary Science, 2026)
The mugger crocodile (Crocodylus palustris), classified as Vulnerable by the IUCN and protected under Schedule I of the Wildlife (Protection) Act, 1972, functions as a keystone wetland predator across the Indian subcontinent. A comprehensive analysis of 2024 Central Zoo Authority (CZA) records from 45 facilities across 12 Indian states (n = 1,187 individuals) revealed an average annual captive population growth of 18.5%, driven primarily by inter-facility transfers rather than natality (78% transfer contribution). Overall mortality was 2.53%, with juveniles (<2 years) accounting for 65% of all deaths, and captive populations exhibited persistent male-biased sex ratios (1.14:1 M:F) with 12.4% unsexed individuals. Facilities employing naturalistic enclosure designs demonstrated significantly higher hatching success than standard concrete enclosures (25.1% vs. 11.6%; F = 6.82, p = 0.02), attributable to thermal gradients (28–34°C), sandy nesting substrates, and seasonal hydrological variation essential for oviposition and temperature-dependent sex determination. Because temperature-dependent sex determination is conserved across multiple reptilian taxa in South and Southeast Asia, these findings have broader regional relevance beyond C. palustris. Evidence-based recommendations include standardized genetic sex determination protocols, ecological enclosure redesign, improved juvenile rearing systems, and integrated captive–wild conservation frameworks to ensure long-term demographic viability and genetic health of this ecologically critical species